Lessons Learned from Nigeria : The Case of Cameroun and Ghana - World Bank (Washington, DC, 2013)
The Nigerian LP Gas Sector Improvement Study of 2004, produced by the Oil and Gas Policy Division with ESMAP funding, lead the Program to draw the lessons learned from the study and to envisage replicating this exercise elsewhere in the Africa Region. The objective of the Nigerian study had been to: (i) investigate and identify reasons for the failure of the LPG market in Nigeria to live up to its potential, (ii) develop a strategy for reviving Nigeria s domestic LPG market, and (iii) expand LPG availability to more consumers including to the poor. The stated quantified objective was to reach the Regional annual average of per capita consumption of 3.4 kg per capita in Nigeria s urban areas, within a reasonable timeframe. In light of the successful outcome of the Nigerian LPG Sector Improvement Study, it has been suggested that lessons learned there should tentatively be applied to other countries likely to benefit from similar investigative and analytical work. Two countries, Cameroon and Ghana, were selected and their current and projected LPG markets were analyzed. They are reported in Volume I (Cameroon) and Volume II (Ghana).